2009
DOI: 10.1213/ane.0b013e31818c7cbd
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Biological Properties of 4-(3-phenyl-[1,2,4] thiadiazol-5-yl)-piperazine-1-carboxylic acid phenylamide, a Mechanism-Based Inhibitor of Fatty Acid Amide Hydrolase

Abstract: Fatty acid amide hydrolase (FAAH) is an integral membrane enzyme within the amidase-signature family. It catalyzes the hydrolysis of several endogenous biologically active lipids, including anandamide (arachidonoyl ethanolamide), oleoyl ethanolamide, and palmitoyl ethanolamide. These endogenous FAAH substrates have been shown to be involved in a variety of physiological and pathological processes, including synaptic regulation, regulation of sleep and feeding, locomotor activity, pain and inflammation. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 43 publications
4
57
0
Order By: Relevance
“…They showed that the decarbamoylation process of FAAH covalent adducts is favored for the piperazinylurea JNJ1661610 (10) [41], with respect to the Oaryl carbamate URB597 (6) [37]. This finding is consistent with the experimental observation of a slowly reversible FAAH inhibition for the piperazinylurea inhibitor and irreversible inhibition for URB597 (6) [33,122].…”
Section: Covalent Inhibition Of Faahsupporting
confidence: 77%
“…They showed that the decarbamoylation process of FAAH covalent adducts is favored for the piperazinylurea JNJ1661610 (10) [41], with respect to the Oaryl carbamate URB597 (6) [37]. This finding is consistent with the experimental observation of a slowly reversible FAAH inhibition for the piperazinylurea inhibitor and irreversible inhibition for URB597 (6) [33,122].…”
Section: Covalent Inhibition Of Faahsupporting
confidence: 77%
“…One dose of JNJ-1661010 (20 mg/kg i.p.) significantly blunted FAAH activity in the rat brain for up to 24 hours and caused a modest ;1.5-fold increase in brain anandamide levels (Keith et al, 2008;Karbarz et al, 2009). JNJ-1661010 administration elicited therapeutic analgesic effects in rat models of neuropathic, inflammatory, and acute thermal pain (Karbarz et al, 2009).…”
Section: A Faah Inhibitorsmentioning
confidence: 97%
“…At least 80 % of enzyme activity was recovered after dialysis of the enzyme-inhibitor complexes for 18 h (see Supporting Information figure S1). In contrast, dialysis of FAAH-URB597 complexes under similar conditions has shown that this agent is an irreversible inhibitor of the enzyme, [39] due to carbamoylation of Ser 241 in the active site. [40] Furthermore, nonlinear regression analysis of the Michaelis-Menten curves demonstrated that all of the selected compounds were noncompetitive inhibitors of FAAH with respect to the natural substrate AEA (see Supporting Information figure S2 A).…”
mentioning
confidence: 99%
“…[39,40] The apparent K i values of compounds 1 b, 1 h, 1 i, 1 j towards FAAH are shown in Table 2. In a second set of experiments, we analyzed the interaction of compounds 1 b, 1 h, 1 i, 1 j with the other targets of the ECS, in order to calculate selectivity index values compared with FAAH (see Table 2).…”
mentioning
confidence: 99%